Analisis Bentuk dan Fungsi Abreviasi dalam Bahasa Generasi Z di Media Sosial Instagram dan TikTok - Musarofah, Musarofah; Imam Baehaqi; Rustanto , Rustanto (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
This research is motivated by the rapid development of social media, particularly Instagram and TikTok, which has influenced the communication patterns of Generation Z and given rise to various forms of abbreviations as a characteristic of digital slang. This phenomenon indicates a change in the form and function of language that is interesting to study linguistically. This study aims to describe the forms of abbreviations that appear in communicative interactions on both platforms and analyze the function of their use in the context of digital communication. The method used is descriptive qualitative because it is appropriate for describing linguistic phenomena naturally without data manipulation. The research data sources are speech, captions, comments, and short conversations from public Instagram and TikTok accounts that actively use slang. Data were selected purposively, considering their relevance to the research focus, namely forms of abbreviations such as abbreviations, acronyms, and syllable shortening. The analysis results show that Generation Z language is very productive in creating abbreviations that are concise, creative, and functional. Abbreviations function not only for communication efficiency but also as markers of group identity, forms of emotional expression, and tools to strengthen social closeness in the digital space. These findings confirm that abbreviation is a linguistic strategy that adapts to the needs of fast and flexible communication in the digital era. The implications of this research demonstrate the importance of understanding the dynamics of slang as part of linguistic change influenced by technology and contemporary popular culture.